TI_GERICHTE 11.2007.133 vom 27. April 2011 , Iscrizione provvisoria di ipoteca legale degli artigiani e imprenditori - TI Tribunale d'appello (2011)
Iscrizione provvisoria di ipoteca legale degli artigiani e imprenditori